A balanced filtering quasi‐Yagi antenna array with sharp roll‐off skirts and high common‐mode suppression. Issue 11 (16th August 2022) - Liu, Xinxin; Zhao, Xi‐Bei; Wei, Feng; Xu, Le; Zhang, Pengfei; Li, Rui
Abstract: In this article, a balanced filtering antenna array with quasi‐Yagi performance is presented. The proposed design is composed of a balanced‐to‐single‐ended power division network, two bandpass filtering units and a linear quasi‐Yagi array including four elements. A steep differential‐mode (DM) passband frequency response is obtained by introducing the triple‐mode folded cross stub‐loaded resonators (FC‐SLRs) in the power division network. The fractional bandwidth and center frequency can be controlled conveniently by adjusting the dimensions of FC‐SLRs. Further, the design procedure is simplified due to the DM responses which are independent of the common‐mode (CM) ones. The proposed antenna array with high gains, good CM rejections, and low cross‐polarization levels is achieved. In addition, three radiation nulls are engendered on the sidebands to improve the selectivity. For demonstrating its feasibility, the balanced antenna prototype is fabricated and measured. The good performances of the proposed balanced filtering antenna array are observed.